2017
DOI: 10.1007/s00259-017-3800-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of atherosclerotic burden and coronary vascular function in patients with suspected coronary artery disease

Abstract: In patients with suspected CAD, CFR provides significant incremental risk stratification over established cardiac risk factors and CAC score for prediction of adverse cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 32 publications
0
29
0
2
Order By: Relevance
“…Assante at al. [8] in a patient population with suspected CAD found that high CAC score is associated with reduced MPR and that both CAC score ≥400 and MPR are signi cant predictors of cardiac events. When the two sides of the coin are evaluated to establish their prognostic value in patients with suspected CAD, it was observed that although both the extent of CAC and the presence of coronary vascular dysfunction are associated with adverse cardiac event, after adjustment for clinical risk, only MPR improve risk assessment [31].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Assante at al. [8] in a patient population with suspected CAD found that high CAC score is associated with reduced MPR and that both CAC score ≥400 and MPR are signi cant predictors of cardiac events. When the two sides of the coin are evaluated to establish their prognostic value in patients with suspected CAD, it was observed that although both the extent of CAC and the presence of coronary vascular dysfunction are associated with adverse cardiac event, after adjustment for clinical risk, only MPR improve risk assessment [31].…”
Section: Discussionmentioning
confidence: 98%
“…By integrating epicardial and microvascular circulations, MPR depicts the vasodilator capacity of the coronary circulation. The added value of MBF and MPR has been demonstrated in the identi cation of impaired coronary vascular function and also as indicator of therapeutic interventions effectiveness [5] and in the prognostic assessment of patient with suspected and known coronary artery disease (CAD) [6][7][8]. Previous studies demonstrated that patients with RH compared with patients with CH have lower value of coronary ow reserve assessed by transthoracic Doppler echocardiography [9] and lower hyperemic MBF and MPR evaluated by 82 Rb PET/CT [10].…”
Section: Introductionmentioning
confidence: 99%
“…A preserved MFR is associated with low probability of coronary atherosclerosis and low risk of cardiac events; on the contrary, a reduced MFR is a significant marker that can help in stratifying CAD risk. [5][6][7][8] However, its diffuse application in the clinical scenario is limited by the technical complexity and elevated operative costs. 9 Previous studies investigated the feasibility of MFR quantification using dynamic scintigraphy and 99m Tc tracers in humans.…”
mentioning
confidence: 99%
“…The relationship between the extent of calcified plaque and the presence of myocardial ischemia has been widely investigated with consistent implications for cardiac risk assessment and prediction. [2][3][4] In particular, inducible myocardial ischemia can be assessed by myocardial perfusion imaging that is a non-invasive imaging test performed so far by two robust techniques: single-photon emission-computed tomography and positron emission tomography. Both methods for myocardial perfusion imaging are considered cornerstones for the diagnostic assessment and risk stratification of patients with suspected coronary artery disease.…”
mentioning
confidence: 99%